Festival Generasi Islami: Silaturahmi Dan Pengembangan Karakter Islami Anak Desa Canggal - Nawang, Mugi; Aidatul, Agustina; Azizah, Ismatul; Alfina, Lina; Wahidah, Baiq Farhatul (Universitas Dehasen Bengkulu, 2025)
The Community Service Program (KKN) is a manifestation of the tridharma of higher education in the form of community service. Canggal Village in Temanggung, where the majority of the population works in the agricultural sector, was chosen as the location for the KKN by Walisongo State Islamic University and Gunung Djati State Islamic University in Bandung. One of the main programs carried out is the Islamic Generation Festival, a competition event for TPQ children from two hamlets in the village, with the aim of strengthening brotherhood and improving Islamic character. The competitions held include the call to prayer, memorization of short letters, calligraphy, and quizzes with Islamic themes. This festival not only aims to improve the Islamic character of children but also as a means of fostering friendship between TPQ teachers in various hamlets. As a result, this festival succeeded in gathering more than 80 participants with high enthusiasm, where participants showed increased self-confidence in developing their potential, especially in the field of religion. This activity is expected to become a routine activity that will continue in the future.